The US trade dispute: Blunt offense or rational strategy? - Michael Hübler; Axel Herdecke (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2019)
This article evaluates the recent protectionist US trade policy and the retaliation of the EU and China. The article employs a New Quantitative Trade Theory model and an Armington model for comparison. The simulation results show that US car tariffs are a credible threat to the EU, but the steel and aluminum tariffs are not. China suffers considerably from the US tariffs, especially the extended, tightened tariffs that have been announced. The retaliation measures of the EU and China, however, do not cause US welfare losses compared to the situation without such a trade policy.
Keywords: F11; F17; F42; 330; Trade policy; trade war; numerical model; USA; EU; China